Testosterone and Vascular Function in Aging - Lopes, Rhéure A.; Neves, Karla B.; Carneiro, Fernando S.; Tostes, Rita (Frontiers in Physiology, 2012)
Androgen receptors are widely distributed in several tissues, including vascular endothelial and smooth muscle cells. Through classic cytosolic androgen receptors or membrane receptors, testosterone induces genomic and non-genomic effects, respectively. Testosterone interferes with the vascular function by increasing the production of pro-inflammatory cytokines and arterial thickness. Experimental evidence indicates that sex steroid hormones, such as testosterone modulate the synthesis and bioavailability of NO and, consequently, endothelial function, which is key for a healthy vasculature. Of interest, aging itself is accompanied by endothelial and vascular smooth muscle dysfunction. Aging-associated decline of testosterone levels is accompanied by age-related diseases, such as metabolic and cardiovascular diseases, indicating that very low levels of androgens may contribute to cardiovascular dysfunction observed in these age-related disorders. Accordingly, testosterone replacement has been shown to have beneficial vascular and metabolic effects. In this mini-review, we briefly comment on the interplay between aging and testosterone levels, the vascular actions of testosterone and its implications for vascular aging. The use of testosterone to prevent vascular dysfunction in elderly is also addressed.